STUDI MORFOLOGI BEBERAPA JENIS LAMUN DI PANTAI TIMUR DAN PANTAI BARAT, CAGAR ALAM PANGANDARAN - Tia Setiawati; Maryam Alifah; Asep Zainal Mutaqin; Mohamad Nurzaman; Budi Irawan; Ruly Budiono (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Sea grass is one component of biodiversity in marine waters composed of many species with various morphological characters. The aim of this study was to obtain the morphological data of seagrass species on the East and West Coasts in Nature Reserve of Pangandaran. The method used was survey method and line transect as far as 200 meters with random sampling technique. Measurements were made for each species of seagrass in the leaf length, leaf width, leaf thickness, stem length and rhizomes length and root length. The results showed that on the East Coast founded three species of seagrass were Cymodocea rotundata, Thalassia hemprichii and Halodule pinifolia, while on the West Coast founded one species of seagrass was Thalassia hemprichii. Cymodocea rotundata has characteristic rounded edges with slight curvature in the middle, Thalassia hemprichii has rounded, brown tip and a brown patterned rhizome, and Halodule pinifolia has side toothed leaf tip with part of the middle there are brown leaf veinsKey words: sea grass, morphology, Pangandaran Nature Reserve